1994
DOI: 10.1007/bf00042942
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the sublethal effects of some petroleum refinery effluents

Abstract: In Canada, environmental regulations for protection of the biota from the adverse effects of effluents from petroleum refineries have tended to focus on acute toxicity. There is concern those effluents may have other subtle, but still deleterious, long-term effects on aquatic ecosystems. We have used a battery of toxicity tests to assess the acute toxicity, genotoxicity, and chronic toxicity of effluent samples from two Ontario refineries. The test organisms included representatives of the bacterial, algal, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…However, petroleum refinery wastewaters are known to carry a variety of mutagenic chemicals (Houk, 1992), but even extracts of these samples were not found to be very potent in comparison to other industrial liquid wastes (McGeorge et al, 1985). And in a study conducted by Sherry et al (1994), one of two petroleum refinery effluents showed genotoxic effects with the SOS Chromotest after having been concentrated ten fold. In the metallurgical plants (15 samples), 10 samples were detected positive without S9 mix and 5 with S9 mix.…”
Section: Genotoxicity Of Whole Effluentsmentioning
confidence: 94%
“…However, petroleum refinery wastewaters are known to carry a variety of mutagenic chemicals (Houk, 1992), but even extracts of these samples were not found to be very potent in comparison to other industrial liquid wastes (McGeorge et al, 1985). And in a study conducted by Sherry et al (1994), one of two petroleum refinery effluents showed genotoxic effects with the SOS Chromotest after having been concentrated ten fold. In the metallurgical plants (15 samples), 10 samples were detected positive without S9 mix and 5 with S9 mix.…”
Section: Genotoxicity Of Whole Effluentsmentioning
confidence: 94%
“…Variations in n ‐alkane levels were used to assess the homogeneity of the composite samples and as a measure of the temporal variability of the effluent over the sample collection period. For the duration of the Oncorhyn‐chus mykiss (rainbow trout) embryo and alevin exposures, 150‐L effluent samples were taken at alternating 4‐ and 3‐d intervals from refinery C. On return to the laboratory, the effluents were mixed, redivided, and stored at 4°C [9].…”
Section: Methodsmentioning
confidence: 99%
“…In a preliminary survey of two Ontario refineries, we used a battery of toxicity tests to assess the acute and sublethal toxicity of effluent samples [9]. That study revealed little evidence of acute toxicity to test organisms from several phyla.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to achieve this is to use biomarkers in fish. 3,4 A biomarker is defined as a biological response to a disturbance, often on the sub-individual level. Since effects at higher hierarchical levels most often are preceded by alterations at lower levels, sub-individual biomarkers can be considered early warning signals of effects on the population or ecosystem levels.…”
Section: Introductionmentioning
confidence: 99%